Assembly and Valence Modulation of Ordered Bimetallic MOFs for Highly Efficient Electrocatalytic Water Oxidation - Yaling Wu; Zhaopeng Sun; Yingying Chen; Dan Liu; Yan Meng; Zheng Yan (Molecules)
Metal synergy can enhance the catalytic performance, and a prefabricated solid precursor can guide the ordered embedding, of secondary metal source ions for the rapid synthesis of bimetallic organic frameworks (MM’-MOFs) with a stoichiometric ratio of 1:1. In this paper, Co-MOF-1D containing well-defined binding sites was synthesized by mechanical ball milling, which was used as a template for the induced introduction of Fe ions to successfully assemble the ordered bimetallic Co1Fe1-MOF-74@2 (where @2 denotes template-directed synthesis of MOF-74). Its electrocatalytic performance is superior to that of the conventional one-step-synthesized Co1Fe1-MOF-74@1 (where @1 denotes one-step synthesis of MOF-74), and the ratio of the two metal sources, Co and Fe, is close to 1:1. Meanwhile, the iron valence states (FeII and FeIII) in Co1Fe1-MOF-74@2 were further regulated to obtain the electrocatalytic materials Co1Fe1(II)-MOF-74@2 and Co1Fe1(III)-MOF-74@2. The electrochemical performance test results confirm that Co1Fe1(II)-MOF-74@2 regulated by valence state has a better catalytic performance than Co1Fe1(III)-MOF-74@2 in the oxygen evolution reaction (OER) process. This phenomenon is related to the gradual increase in the valence state of Fe ions in Co1Fe1(II)-MOF-74@2, which promotes the continuous improvement in the performance of the MOF before reaching the optimal steady state and makes the OER performance reach the optimum when the FeII/FeIII mixed-valence state reaches a certain proportion. This provides a new idea for the directed synthesis and optimization of highly efficient catalysts.